Study of the Electricity Generating from Low Wind Speed in Thailand - พลาศัย, วสันต์ (Princess of Naradhiwas University Journal, 2018)
This research studied the ability to produce electricity from low wind speed in Thailand from multiblades wind turbines for compressed air with CFD program to predict the results by spending less time, saving budget to create a high cost structures. The model shows the flow of air in a turbulent flow, wind speed that affects the lifting of the turbine blade. The configuration method used in the model is Tetrahedra Cells in CFD. The minimum wind speed is varied 1m / s and the maximum wind speed is 5m / s and the torque is 2.54076 N.m and 64.0231 N.m, respectively, there were 3915694 Nodes. The consistency in the same direction can bring results from the model to the calculation to create multiblades wind turbines for compressed air energy storage systems for electrical generation.